Aesthetic Experience of Local Cultural Tourism Meron to Encourages Creativity Among Early Childhood in Indonesia - Fajrie, Nur; Widjanarko, Moch; Alam, Fatkur; Marmoah, Sri; Pratama, Hendri (Journal of Advanced Research Design, 2025)
This study explores the integration of local cultural elements and environmental materials (loose parts) in fostering aesthetic development in early childhood education. The research aims to analyze aesthetic experiences of early childhood in Sukolilo related to the Meron cultural tradition, assess how culture-based learning enhances these experiences, and identify supporting factors. Using a mixed-methods approach, the study includes Playgroup students aged 4-5 years from Sukolilo, with data collected through surveys, interviews, observations, and document analysis. Results indicate moderate aesthetic experiences, with children successfully recreating Meron shapes, highlighting the effectiveness of integrating culture and loose parts in promoting creativity.